Predicting response to immunosuppressive therapy in childhood aplastic anemia - Nao Yoshida; Hiroshi Yagasaki; Asahito Hama; Yu Takahashi; Yoshiyuki Kosaka; R Kobayashi; Hiromasa Yabe; Takashi Kaneko; Masahiro Tsuchida; Akira Ohara; Tatsutoshi Nakahata; Seiji Kojima (2011)
In aplastic anemia, predictive markers of response to immunosuppressive therapy have not been well defined. We retrospectively evaluated whether clinical and laboratory findings before treatment could predict response in a pediatric cohort from the multicenter AA-97 study in Japan. Between 1997 and 2006, 312 newly diagnosed children were enrolled and treated with a combination of antithymocyte globulin and cyclosporine. In multivariate analyses, lower white blood cell count was the most significant predictive marker of better response; patients with white blood cell count less than 2.0×109/L showed a higher response rate than those with white blood cell count of 2.0×109/L or more (P=0.0003), followed by shorter interval between diagnosis and therapy (P=0.01), and male sex (P=0.03). In conclusion, pre-treatment clinical and laboratory findings influence response to therapy. The finding that response rate worsens with increasing interval between diagnosis and treatment highlights the importance of prompt immunosuppressive therapy for patients with aplastic anemia.